Integrative-mediation methodology for developing pre-service English teachers’ language skills and cultural mediation competence - Jakbarova, Nasibahon (The Lingua Spectrum, 2026)
This article presents the theoretical foundations and empirical outcomes of an Integrative-Mediation Methodology (IMM) designed to simultaneously develop language skills and cultural mediation competence in pre-service English language teachers. Grounded in sociocultural theory, intercultural communicative competence frameworks, and task-based language teaching, IMM integrates specialist subject content across four skill areas — reading, listening, speaking, and writing — through a structured system of integrative-mediative exercises organised in a five-level hierarchy. An experimental study involving 94 pre-service English teachers at Namangan State Institute of Foreign Languages was conducted over two academic semesters (2023–2025). Results demonstrated statistically significant gains in all four language skills and in cultural mediation competence among participants in the experimental group compared to the control group, with effect sizes ranging from d=0.71 to d=1.02. Qualitative data from reflective journals and focus-group interviews corroborated the quantitative findings, identifying five mechanisms through which IMM accelerates language and intercultural development. The article proposes a replicable model for IMM implementation in pre-service ELT programmes across non-Anglo higher education contexts.